Spatial distribution of soil quality under different vegetation types in the Yellow River Delta wetland - Sun, Debin; Li, Yunzhao; Yu, Junbao; Li, Baoquan; Guan, Bo; Zhou, Di; Wang, Xuehong; Yang, Jisong; Ma, Yuanqing; Zhang, Xin; Li, Xue; Ling, Yue; et al. (Frontiers in Ecology and Evolution, 2022)
The soils from four typical natural wetlands of Phragmites australis wetland, Tamarix chinensis wetland, Suaeda salsa wetland and tidal flat, as well as crop land, were selected to evaluate the soil quality in the Yellow River Delta. 14 soil physicochemical property indexes were employed to build a minimum data set (MDS). Combined with vegetation type and soil depth, the soil quality index (SQI) was conducted. A fuzzy logic model was applied for data normalization. The contrast test was conducted to verify the accuracy of MDS. The results showed that the MDS consists of TOC, NO3–N, Sa, TS, TP, Mg, C/N and pH. The soil quality decreased from the inland to coastline and from crop land to tidal flat with the change of vegetation type. The soil quality of 0-10 cm soil depth was obviously better than that of 20-30 cm soil depth. The soil qualities of crop land were significantly better than those of natural wetlands at the same soil depth. Correlation analysis results showed that agricultural reclamation has become an important factor of soil quality change in study area. Comparative results of two methods of MDS and TDS testified that the method of MDS was credible and accurate for soil quality assessment of study area. Our results indicated that the wetland protection and agricultural reclamation in coastal aera should keep a rational balance.